KESESUAIAN DAN DAYA DUKUNG KAWASAN PANTAI RONELA BAGI PENGEMBANGAN EKOWISATA Di DUSUN RUMAH OLAT KECAMATAN SERAM UTARA - Merlin Latutiene; Henderina Lelloltery; M. M.S Putileihalat (Jurnal Sylva Scienteae, 2023)
This study aims to determine the suitability of Ronela Beach Tourism for the Development of Ronela Beach Ecotourism and to analyze the carrying capacity of the Ronela Beach area for Coastal Ecotourism Activities. The method used in this research is survey method with descriptive analysis. To describe in a systematic, factual and accurate manner regarding the suitability and carrying capacity of the Ronela Beach Area for the Development of Coastal Ecotourism in Rumah Olat Hamlet. Data collection techniques used by researchers in this study are interview and observation techniques. The results of the study show that the Ronela beach area is very suitable for beach ecotourism activities with a beach tourism suitability index value of 83.3% including the "Very Suitable" category. The physical carrying capacity of the area is 300 people/dayPenelitian ini bertujuan untuk mengetahui Kesesuaian Wisata Pantai Ronela Bagi Pengembangan Ekowisata Pantai Ronela dan Menganalisis Daya Dukung Kawasan Pantai Ronela Bagi Kegiatan Ekowisata Pantai. Metode yang digunakan dalam penelitian ini yaitu metode survey dengan analisis deskriptif. Untuk mendeskriptifkan secara sistematis, faktual dan akurat mengenai Kesesuaian dan Daya Dukung Kawasan Pantai Ronela Bagi Pengembangan Ekowisata Pantai di Dusun Rumah Olat. Teknik pengumpulan data yang di gunakan dalam penelitian ini yaitu teknik wawancara dan observasi. Hasil penelitian menunjukan bahwa kawasan pantai Ronela sangat sesuai untuk kegiatan ekowisata pantai dengan nilai indeks kesesuaian wisata pantai adalah 83,3 % termasuk kategori “Sangat Sesuai” .dan Daya dukung fisik kawasan sebesar 300 orang/hari